1964
DOI: 10.1099/00221287-34-3-475
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Production and Assay of Interferon

Abstract: SIJMMARYInterferon was produced in chick embryo cell cultures orjn chick embryos by five viruses and in mouse embryo cell cultures or mouse lungs by two viruses. The slopes of the log dose response lines for the five chick interferons were compared by using vaccinia virus as the assay virus. Analysis of variance showed that they did not differ significantly. Partially purified interferon gave the same slope as the crude preparations. These findings allowed a comparison to be made of relative yields of interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1965
1965
1974
1974

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Primary chick embryo cell cultures were prepared from 9-to 10-day-old embryos as previously described (4). At the time of use, usually 40 to 48 hours later, the cultures contained about 4 million cells on a glass surface area of 18 em 2.…”
Section: Introductionmentioning
confidence: 99%
“…Primary chick embryo cell cultures were prepared from 9-to 10-day-old embryos as previously described (4). At the time of use, usually 40 to 48 hours later, the cultures contained about 4 million cells on a glass surface area of 18 em 2.…”
Section: Introductionmentioning
confidence: 99%
“…Interferon preparations induced in chick embryo cell cultures by several viruses gave parallel dose response curves allowing estimates to be made of the relative potencies of each interferon preparation ( 1). When different viruses are employed to assay an interferon preparation the slope of the dose response lines may differ significantly ( 1).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon was produced by inoculating chick embryo cell cultures with chikungunya virus ( 1 ) . The procedure was often modified in that the cultures were inoculated with virus immediately after dispensation of cells.…”
Section: Materials and Methods Media And Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparative study of the production of interferon by different viruses, G i f f d et aZ (2) showed that chikungunya viilus produced 2.6 times more interferon than did Semliki Forest virus when an input lmultiplicity of 0.06 PFU per cell was employed for the 2 viruses. Since it had not been established that this multiplicity of Semliki Forest v i m resulted in maximum production of interferon, the comparison 04 the efficiency of the 2 viruses may not be valid under all conditions.…”
mentioning
confidence: 99%